2012
DOI: 10.1128/aac.00259-12
|View full text |Cite|
|
Sign up to set email alerts
|

Levofloxacin Inhibits Rhinovirus Infection in Primary Cultures of Human Tracheal Epithelial Cells

Abstract: ABSTRACTRespiratory virus infections, including infections with rhinoviruses (RVs), are related to exacerbations of chronic obstructive pulmonary disease (COPD). A new quinolone antibiotic, levofloxacin (LVFX), has been used to treat bacterial infections that cause COPD exacerbations as well as bacterial infections that are secondary to viral infection in COPD patients. However, the inhibitory effects of LVFX on RV infection and RV infection-induced airway inflammation have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Our immunohistochemical findings show this activation to occur in isolated cells that could correspond to infiltrating leukocytes, although the lack of double immunostaining precludes any firm conclusion. It has been reported that both macrolides [28] and quinolones [29] may block NFκB activation, resembling our own results. However, we did not find any differences in Cxcl2 expression that could explain the decreased neutrophilic infiltrates in animals receiving clarithromycin.…”
Section: Discussionsupporting
confidence: 92%
“…Our immunohistochemical findings show this activation to occur in isolated cells that could correspond to infiltrating leukocytes, although the lack of double immunostaining precludes any firm conclusion. It has been reported that both macrolides [28] and quinolones [29] may block NFκB activation, resembling our own results. However, we did not find any differences in Cxcl2 expression that could explain the decreased neutrophilic infiltrates in animals receiving clarithromycin.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, levofloxacin has been found to inhibit HRV infection in primary cell cultures employing human tracheal epithelial cells. 188 Levofloxacin pretreatment decreased mRNA levels of ICAM-1. Macrolides have also been reported to reduce ICAM-1 expression and HRV-induced cytokines in vitro and in vivo.…”
Section: Treatmentmentioning
confidence: 98%
“…Furthermore, fluoroquinolones have been shown to suppress hepatitis C virus (HCV, family Flaviviridae) replication in vitro, possibly by inhibiting the viral helicase [32], but this suppression has not translated into an effective treatment for patients with liver failure due to chronic HCV infection [33]. Additionally, fluoroquinolones suppress rhinovirus infection by reducing expression of the viral receptor on cells [34]. Recently, Xu et al demonstrated that a high concentration of enoxacin administered to human neuronal progenitor cells (hNPC) and brain organoids prior to and after infection with ZIKV suppressed viral replication and restored normal cellular proliferation, possibly by enhancing RNAi [35].…”
Section: Introductionmentioning
confidence: 99%